Chrysotus capellarii sp. nov., the first species of longipalpus group from Colombia (Diptera: Dolichopodidae) - Soares, Matheus Mickael Mota; Carvalho-Filho, Fernando; Ramos-Pastrana, Yardany (EntomoBrasilis, 2023)
Chrysotus capellarii Soares & Carvalho-Filho sp. nov. is described and illustrated based on a single specimen collected in the department of Córdoba, Colombia, representing the first record of the longipalpus species group from the country (a photographic record is known from Costa Rica). The new species is easily recognized by the long palpus (about 2x longer than eye height) with a wide and oval apical lamella.